The mathematical method for assessing the cybersecurity state of cloud services - Ivanchenko, Yevheniia; Shulha, Volodymyr; Ivanchenko, Ihor; Pedchenko, Yevhenii; Petrovska, Mari (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
This study presents the developed mathematical method for assessing the cybersecurity state of cloud services of information infrastructure facilities. The developed assessment method consists of 11 assessment stages, which provide a comprehensive assessment of 5 types of cloud services. The developed approach to assessing the cybersecurity state of cloud services can become the basis for further research in the field of cybersecurity by expanding tools for analyzing risks in the cloud environment and will help increase confidence in the use of cloud services in the face of modern information challenges.